2019
DOI: 10.2147/tcrm.s195802
|View full text |Cite
|
Sign up to set email alerts
|

<p>Incidence, clinical features, and risk factors of fluoroquinolone-induced acute liver injury: a case-control study</p>

Abstract: BackgroundFluoroquinolone-related hepatotoxicity is rare but serious and is attracting increasing attention. We explored the incidence, clinical features and risk factors of acute liver injury associated with fluoroquinolone use.Materials and methodsBased on the Adverse Drug Events Active Surveillance and Assessment System that we developed, we carried out a case-control study by enrolling patients who were hospitalized and received fluoroquinolones to treat or prevent infections at the Chinese People’s Libera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 37 publications
2
13
0
2
Order By: Relevance
“…Liver dysfunction is a rare adverse effect of fluoroquinolone, but serious. Although the mechanism of fluoroquinolone‐induced liver dysfunction is still unknown, many reports indicated that this adverse effect may be because of the immunoallergic reaction 50 . Also, DM is one of the diseases that is associated with electrolyte abnormalities 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Liver dysfunction is a rare adverse effect of fluoroquinolone, but serious. Although the mechanism of fluoroquinolone‐induced liver dysfunction is still unknown, many reports indicated that this adverse effect may be because of the immunoallergic reaction 50 . Also, DM is one of the diseases that is associated with electrolyte abnormalities 51 .…”
Section: Discussionmentioning
confidence: 99%
“…The system is an adverse event warning system independently developed by our hospital that can automatically retrieve and alert the staff about suspected patients according to condition settings to improve work efficiency. The stability and accuracy of the system have been verified many times 6,8,9 . The researchers then screened the suspected patients.…”
Section: Methodsmentioning
confidence: 99%
“…The ADE-ASAS is based on trigger technology and text recognition technology, which can be connected to the HIS to extract patient information. Intelligent active surveillance of a single drug in multiple ADR modules can be accomplished [ 14 , 15 ]. The accuracy of this system has been evaluated in multiple studies, with a positive predictive value reaching 69.4% [ 15 , 16 ].…”
Section: Methodsmentioning
confidence: 99%